Internal drainage of pancreatic pseudocyst following abdominal blunt trauma - Siti Fatimah; Emiliana Lia (Journal of Pediatric Surgery Case Reports, 2022)
Purpose: Pancreatic pseudocyst is a well-recognized complication of acute pancreatitis, chronic pancreatitis and pancreatic trauma. Pancreatic trauma is the most common cause among children cases. The aim of this study is to describe the clinical presentation and management of symptomatic pancreatic pseudocyst in a series of 2 children following abdominal blunt trauma treated in our institution between January 2021 to August 2021. Method: This was single-centre case series from our institution that is a tertiary referral hospital from January to August 2021. There were two patients between age 8–11 that diagnosed with pancreatic pseudocyst after blunt abdominal trauma, both of them underwent open internal drainage, specifically cystojejunostomy. Result: All of 2 patients had a history of blunt abdominal trauma due to bicycle handlebar injury. Epigastric pain and abdominal mass were the main complaints. Amylase and lipase serum level were elevated and imaging diagnostic reveal pancreatic pseudocyst. Open cystojejunostomy were performed and the patient discharged from the hospital on day 7 and day 11 post operative, respectively, without any complication. Conclusion: Pancreatic pseudocyst although rare in children, can lead to a significant morbidity if not properly diagnosed and treated. Open internal drainage is still the procedure of choice in our institution.